A morphological review of tribes in Larentiinae (Lepidoptera: Geometridae) - Viidalepp, Jaan (Zootaxa, 2011)
Tribes of looper moths (Geometridae: Larentiinae) are reviewed. The tribe Dyspteridini Hulst is reinstated (previously synonymous with the Trichopterygini Warren). A new subtribe, Aplocerina, is separated from the Chesiadini Pierce, and the group Ortholithinae Pierce is dealt with as Scotopterygini Warren, the sister taxon to Xanthorhoini. Morphological traits for 22 of 23 larentiine tribes represented in the Holarctic fauna are listed and illustrated. A taxonomy of the subfamily Larentiinae is proposed and supported, using morphological data based on chemical communication structures and male genitalia. A new combination is presented: Melanthia mandshuricata (Bremer), transferred from Mesoleuca Hübner (Larentiini)